Aryl hydrocarbon receptor affects circadian-regulated lipolysis through an E-Box-dependent mechanism. (1st January 2023) - Khazaal, Ali Qasim; Haque, Nazmul; Krager, Callie R.; Krager, Stacey L.; Chambers, Christopher; Wilber, Andrew; Tischkau, Shelley A.
Abstract: An internal circadian clock regulates timing of systemic energy homeostasis. The central clock in the hypothalamic suprachiasmatic nucleus (SCN) directs local clocks in peripheral tissues such as liver, muscle, and adipose tissue to synchronize metabolism with food intake and rest/activity cycles. Aryl hydrocarbon receptor (AhR) interacts with the molecular circadian clockworks. Activation of AhR dampens rhythmic expression of core clock genes, which may lead to metabolic dysfunction. Given the importance of appropriately-timed adipose tissue function to regulation of energy homeostasis, this study focused on mechanisms by which AhR may influence clock-controlled adipose tissue activity. We hypothesized that AhR activation in adipose tissue would impair lipolysis by dampening adipose rhythms, leading to a decreased lipolysis rate during fasting, and subsequently, altered serum glucose concentrations. Levels of clock gene and lipolysis gene transcripts in mouse mesenchymal stem cells (BMSCs) differentiated into mature adipocytes were suppressed by the AhR agonist β-napthoflavone (BNF), in an AhR dependent manner. BNF altered rhythms of core clock gene and lipolysis gene transcripts in C57bl6/J mice. BNF reduced serum free fatty acids, glycerol and liver glycogen. Chromatin immunoprecipitation indicated that BNF increased binding of AhR to E-Box elements in clock gene and lipolysis gene promoters. These data establish a link between AhR activation and impaired lipolysis, specifically by altering adipose tissue rhythmicity. In response to the decreased available energy from impaired lipolysis, the body increases glycogenolysis, thereby degrading more glycogen to provide necessary energy. Highlights: AhR activation suppresses clock genes and lipolysis genes in vitro in adipocytes derived from BMSCs. AhR activation suppresses circadian clock function in white adipose tissue in vivo . AhR may act as a repressor to inhibit CLOCK:BMAL1 transactivation of target genes that contain E-Box elements. Activation of AhR alters white adipose tissue function to alter system metabolism.